4(w+5)=-2(5w-8)+6w

Simple and best practice solution for 4(w+5)=-2(5w-8)+6w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(w+5)=-2(5w-8)+6w equation:


Simplifying
4(w + 5) = -2(5w + -8) + 6w

Reorder the terms:
4(5 + w) = -2(5w + -8) + 6w
(5 * 4 + w * 4) = -2(5w + -8) + 6w
(20 + 4w) = -2(5w + -8) + 6w

Reorder the terms:
20 + 4w = -2(-8 + 5w) + 6w
20 + 4w = (-8 * -2 + 5w * -2) + 6w
20 + 4w = (16 + -10w) + 6w

Combine like terms: -10w + 6w = -4w
20 + 4w = 16 + -4w

Solving
20 + 4w = 16 + -4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '4w' to each side of the equation.
20 + 4w + 4w = 16 + -4w + 4w

Combine like terms: 4w + 4w = 8w
20 + 8w = 16 + -4w + 4w

Combine like terms: -4w + 4w = 0
20 + 8w = 16 + 0
20 + 8w = 16

Add '-20' to each side of the equation.
20 + -20 + 8w = 16 + -20

Combine like terms: 20 + -20 = 0
0 + 8w = 16 + -20
8w = 16 + -20

Combine like terms: 16 + -20 = -4
8w = -4

Divide each side by '8'.
w = -0.5

Simplifying
w = -0.5

See similar equations:

| 12m=12+11m | | -(2-3(2.2))+2.2= | | 6a+19=44 | | 3.8+8.93=-17.29 | | 1a+6a-21b= | | -10p+11=-9p | | 16-6(-3+4)=28 | | -10+9+(-11)+(-29)= | | 6x=9-1 | | 34x+16+30x=52x+100 | | 3(8-x)+5=2x | | x+8=2(y+8) | | .67x+.5=6.50 | | 4(3+3)=3(3x-1) | | -20-11q=-7q | | 20+4=14 | | 3w+7-2(-6w-2)=3(w-1) | | 7+8lnx=55 | | 9(x)=3(40) | | 6(x-1)=8-2[4-2(x+1)] | | 16-6(-3x+4)=28 | | 180=x-0.04x | | 3x=19.5 | | 10x+y+32=63 | | 11-v=8 | | 2x+(x+9)=90 | | 6(3-x)=-(2+2x) | | 7x-50=180 | | 3x+(4-2x)=16 | | -3(x+4)=-36 | | -4(2x+3)=2x+6(8x+2) | | 14+9x=5x+62 |

Equations solver categories